Alkali residue-coal gangue based carbon dioxide carbonized coal gangue concrete and preparation method thereof

By using alkali slag-coal gangue carbon dioxide carbonization technology in concrete, the problems of compressive strength and chloride ion penetration in the existing technology are solved, and efficient solid waste recycling and performance improvement are achieved.

CN119797840APending Publication Date: 2025-04-11GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411981667.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the compressive strength of concrete and reduce the chloride ion permeability coefficient, resulting in a decrease in the strength and durability of concrete structures.

Method used

Carbon dioxide carbonized coal gangue concrete technology based on alkali slag-coal gangue is adopted to absorb free water in the cement slurry through coal gangue, reduce the drying shrinkage rate, and perform a secondary hydration reaction during the carbonization process to fill the internal pores of the cement, improve density, and reduce the diffusion rate of chloride ions.

Benefits of technology

It significantly improves the compressive strength of concrete, reduces the chloride ion flux, extends the durability of concrete, and realizes the recycling of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221697210000071
    Figure BDA0005221697210000071
  • Figure BDA0005221697210000081
    Figure BDA0005221697210000081
  • Figure BDA0005221697210000082
    Figure BDA0005221697210000082
Patent Text Reader

Abstract

The invention discloses carbon dioxide and carbonized coal gangue concrete based on alkaline residue-coal gangue, and the carbonized coal gangue concrete comprises the following raw materials in percentage by mass: 10-20% of alkaline residue, 20-40% of coal gangue, 40-60% of cement, 5-15% of calcium sulfate and 5-15% of deionized water, and the total mass is 100%. The coal gangue has the effect of improving the strength; the effect of reducing the shrinkage rate is achieved. The preparation method comprises the following steps: 1, pretreating the raw materials; 2, preparation of coal gangue concrete slurry; 3, marking and curing the coal gangue concrete slurry; and 4, carbon dioxide carbonization of the coal gangue concrete. When the coal gangue concrete is applied as carbonized coal gangue concrete and the adding amount of the coal gangue accounts for 33% of the total mass, the chloride ion electric flux is 1150-1250 Coulombs, the compressive strength is 75.5-76.5 MPa, and the drying shrinkage rate is 1.20-1.30 * 10 <-3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue and a preparation method thereof. Background Art

[0002] As an important building material, traditional cement consumes a large amount of raw materials represented by limestone during the production process. In addition, traditional cement can no longer meet the current engineering construction requirements for cement's corrosion resistance, durability and compressive strength. At the same time, solid waste, referred to as solid waste, is also a common problem in the industrial field. For example, coal mining produces a large amount of coal gangue. The accumulation of coal gangue occupies a large amount of land resources, leading to landslides and spontaneous combustion problems; and in the chemical industry and other industries, improper disposal of alkali slag will cause serious pollution to the soil and water. Common solutions include solid waste recycling methods, which adopt the method of mixing solid waste into concrete to prepare modified cement, so as to achieve the purpose of resource recovery, full utilization of resources and reduction of production costs.

[0003] Among them, adding coal gangue to cement can improve the compressive strength of cement. The basic principle is that during the cement hydration process, coal gangue can react with calcium hydroxide and other components in cement to generate cementitious substances, thereby improving the strength and durability of cement. For example, in the existing literature 1 (Liu Chaoqun, Zhu Zewen, Zhang Youhua, et al. Study on the hydration mechanism and performance of activated coal gangue cement [J]. Bulletin of the Chinese Ceramic Society, 2023, 42(10): 3660-3670. DOI: 10.16552 / j.cnki.issn1001-1625.20230923.006.), the 28d compressive strength of the specimens mixed with 30% activated coal gangue was increased by 11.82% compared with the specimens mixed with 30% quartz powder. In this technical solution, the role of coal gangue is mainly reflected in the reaction of a large amount of active SiO2 and Al2O3 with Ca(OH)2 in cement hydration products to generate a large amount of secondary hydration products. However, in order to achieve the above technical effects, the cement in this technical solution maintains a high alkalinity, and there are a large number of chloride ions in the cement, which directly causes the chloride ions to be adsorbed on the surface of the steel bars and react with the iron hydroxide in the steel bars to form a soluble ferric chloride complex, which leads to a sharp decrease in the strength and durability of the concrete structure, which is reflected in the increase of chloride ion flux, that is, the problem of high chloride ion diffusion coefficient.

[0004] In order to solve the problem of high chloride ion diffusion coefficient mentioned above, materials with low chloride ion content can be used as additives. For example, the existing document 2 (Zhang Yi, Duan Zhenyu, Zhang Tianxiao, et al. Experimental study on mechanical properties and impermeability of modified rubber cement-based materials [J / OL]. Journal of Inner Mongolia University of Technology (Natural Science Edition), 1-8 [2024-12-27]. https: / / doi.org / 10.13785 / j.cnki.nmggydxxbzrkxb.2025.02.007.) reduces the chloride ion diffusion coefficient by 63.2% by adding 30% rubber. This technical solution uses the capillary force of rubber particles to reduce the chloride ion permeability by reducing the impermeability. However, since rubber is an inert material, it only physically reacts with cement and does not react chemically. At the same time, the introduction of rubber particles will also introduce bubbles into the cement-based material, which will significantly reduce the compressive strength of the concrete. In addition, rubber is a chemical raw material, and its use value and cost are much higher than solid waste, that is, the purpose of solid waste recycling cannot be achieved.

[0005] In order to solve the above-mentioned compressive strength problem, cement can be carbonized to improve concrete performance. For example, in existing literature 3 (Li Yadong. Research on mechanical properties and carbonization resistance of alkali-activated coal gangue-fly ash geopolymer concrete [D]. Zhongyuan University of Technology, 2024. DOI: 10.27774 / d.cnki.gzygx.2024.000022.), by adding coal gangue and performing carbonization operation, the compressive strength reaches up to 50.6MPa, which is 43.5% higher than the compressive strength of cement without carbonization operation. However, in order to improve the compressive strength of this technical solution, a large amount of coal gangue needs to be added, and as mentioned above, the chloride ion permeability coefficient is positively correlated with the amount of coal gangue added. That is to say, although this technical solution significantly improves the compressive strength, it also significantly increases the chloride ion permeability coefficient, resulting in the steel bars in the concrete being more susceptible to corrosion and unable to meet the application requirements.

[0006] The inventors of the present invention have previously shown that the use of co-adding steel slag, alkali slag and fly ash as additives can solve the problems of compressive strength and chloride ion penetration at the same time. Existing document 4 (Zou Yongjin, Zhu Houqi, Wang Shunxiang, et al. A solid waste recycled foam concrete based on steel slag-alkali slag-fly ash [P]. Guangxi Zhuang Autonomous Region: CN202410882677.6, 2024-10-22.). By co-adding steel slag, alkali slag and fly ash to prepare foamed concrete, the compressive strength is improved and the chloride ion permeability coefficient is reduced. The compressive strength of the foamed concrete is increased to 37.5MPa, and the chloride ion diffusion coefficient is reduced to 1.022×10 -8 However, subsequent studies have found that among the raw materials of this technical solution, steel slag has a lower effect on improving compressive strength than coal gangue.

[0007] Through the analysis of the above literature, it can be seen that the current technical solutions for improving a single performance cannot achieve the technical effect of comprehensive performance meeting application requirements; and the current technical solutions for simultaneously improving compressive strength and chloride ion penetration cannot achieve the technical effect of improving a single performance. Summary of the invention

[0008] The purpose of the present invention is to provide a carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue and a preparation method thereof. In view of the problems existing in the prior art, the basic technical principle of the present invention is:

[0009] Coal gangue is used to absorb free water in cement paste, that is, to reduce the content of free water in cement paste. Its function is to achieve internal curing in the drying process, reduce water evaporation, and ultimately achieve the effect of reducing drying shrinkage. At the same time, during the carbonization process, coal gangue and cement undergo secondary hydration reaction to fill the internal pores of cement, refine the pores, improve the density, reduce the migration channels of chloride ions, reduce the diffusion rate of chloride ions, and ultimately achieve the reduction of chloride ion flux. In addition, there are SiO2 and Al2O3 in the coal gangue components, and the gel product generated during the carbonization operation further fills the pores, that is, forms a denser structure, thereby significantly improving the compressive strength.

[0010] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0011] A carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue, the raw materials and their mass percentages of the carbonized coal gangue concrete are: alkali slag: 10-20%, coal gangue: 20-40%, cement: 40-60%, calcium sulfate: 5-15%, deionized water: 5-15%, and the total mass is 100%;

[0012] The cement is 42.5 grade ordinary Portland cement;

[0013] The gangue has the function of increasing strength and reducing shrinkage.

[0014] The coal gangue has the following components in percentage by mass: 30-60% silicon dioxide, 15-35% aluminum oxide, 2-10% iron oxide, 1-10% calcium oxide, and 10-30% carbonaceous matter; the particle size of the coal gangue is no greater than 5 mm;

[0015] The role of the coal gangue in the technical solution is that silicon dioxide and aluminum oxide, as active substances, have volcanic ash activity and hydraulic gelling properties. During the cement hydration process, they can react with calcium hydroxide in cement to generate a gelling substance, thereby improving the strength and durability of cement.

[0016] The coal gangue is pre-treated, that is, ground by a ball mill to obtain coal gangue powder, and the powder density of the coal gangue powder is 2.0-2.5g / cm 3 , specific surface area 300-600m 2 / Kg;

[0017] The composition and mass percentage of the alkali residue are: 60-65% calcium carbonate, 10-15% calcium chloride, and 28-15% calcium hydroxide; the particle size of the alkali residue is not greater than 75 μm;

[0018] The alkali residue has a calcium content of 60-80%;

[0019] The role of the alkali residue in the technical solution is that it is rich in calcium and forms active calcium hydroxide during the preparation process;

[0020] The alkali residue is pretreated to obtain chlorine-free alkali residue, and the alkali residue is dechlorinated to obtain chlorine-free alkali residue, and the chlorine content of the chlorine-free alkali residue is less than 0.3%.

[0021] A method for preparing carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue comprises the following steps:

[0022] Step 1, pretreatment of raw materials, pretreatment of raw materials alkali residue, coal gangue, cement, and calcium sulfate;

[0023] Step 1.1, pretreatment of alkali residue and calcium sulfate, first, washing the alkali residue with water under certain conditions to obtain chlorine-free alkali residue, then calcining the chlorine-free alkali residue under certain conditions, wherein the by-product hydrogen chloride produced by the calcination can be recycled, and finally, washing the calcined product with water to obtain calcium hydroxide, and then mixing the calcium hydroxide and calcium sulfate in a certain mass ratio to obtain an activator;

[0024] In the step 1.1, the water washing condition is a water-to-solid ratio of 6:1, and the number of water washings is 3-5 times;

[0025] In the step 1.1, the calcination conditions are: the calcination temperature is 850-1000°C, and the calcination time is 45-60min;

[0026] In the step 1.1, the mass ratio of calcium hydroxide to calcium sulfate is 3:2;

[0027] Step 1.2, pretreatment of coal gangue, first, placing coal gangue and deionized water in a hot stuffy tank, and subjecting the coal gangue to hot stuffy aging under certain conditions, so that the active silica and alumina in the coal gangue fully react to generate a gelling substance, thereby improving the stability of the coal gangue, and then, under certain conditions, ball milling the coal gangue to obtain coal gangue powder;

[0028] In the step 1.2, the heat-stuffing aging condition is, under a closed condition, a heat-stuffing temperature of 100-300° C.;

[0029] In the step 1.2, the ball milling conditions are: under air conditions, the ball milling speed is 150-300 r / min, and the ball milling time is 4-5 h;

[0030] Step 2, preparation of coal gangue concrete slurry, with the coal gangue powder obtained in step 1.2 accounting for a certain proportion of the total mass, cement and coal gangue powder are mixed, and stirred under certain conditions to obtain a multi-component admixture mixture, referred to as the mixture, and then, the mixture and deionized water are mixed in a certain mass ratio, and stirred under certain conditions to obtain coal gangue concrete slurry;

[0031] In step 2, the coal gangue powder accounts for 33-39% of the total mass;

[0032] In step 2, the stirring condition for preparing the mixture is 15-20 minutes; the stirring condition for preparing the gangue concrete slurry is 25-30 minutes;

[0033] In step 2, the mass ratio of the mixture to deionized water is 1:0.5;

[0034] Step 3, standard curing of the gangue concrete slurry, first, the gangue concrete slurry obtained in step 2 is formed, and then cured under standard curing conditions. After the curing is completed, it is naturally dried indoors for 2 days to obtain gangue concrete, referred to as D165-M56;

[0035] In step 3, the standard curing conditions are: the curing temperature is 20±2°C, the relative humidity is above 95%, and the curing time is 56 days;

[0036] Step 4, carbon dioxide carbonization of coal gangue concrete, first, placing 25 mm thick wet sand at the bottom of the carbonation box, then carbonizing with carbon dioxide under carbon dioxide gas conditions, referred to as carbonization, to obtain carbonized coal gangue concrete, referred to as D165-M56-C4;

[0037] In step 4, the carbonization conditions are: a carbon dioxide concentration of 20%±3%, a relative humidity of more than 95%, a carbonization temperature of 20±5° C., and a carbonization time of 4 hours.

[0038] When the carbonized coal gangue concrete based on alkali slag-coal gangue is used as the carbonized coal gangue concrete, when the addition amount of coal gangue accounts for 33% of the total mass, the chloride ion flux is 1150-1250 Coulombs, the compressive strength is 75.5-76.5MPa, and the drying shrinkage is 1.20-1.30×10 -3 .

[0039] The technical effect of the carbon dioxide carbonized coal gangue concrete obtained by the alkali slag-coal gangue of the present invention is as follows:

[0040] The test results of chloride ion flux show that the addition of coal gangue can increase the chloride ion flux, which can be reduced under 4h carbonation operation. When the addition of coal gangue accounts for 33% of the total mass, the flux of 56d carbonized coal gangue concrete is reduced to 1200 Coulombs.

[0041] The test results of the test block method show that the addition of coal gangue can improve the strength of carbonized coal gangue concrete. When the addition of coal gangue accounts for 33% of the total mass, the compressive strength of 56d carbonized coal gangue concrete increases to 75.9MPa.

[0042] The drying shrinkage test results show that the addition of coal gangue can reduce the drying shrinkage of carbonized coal gangue concrete. When the addition of coal gangue accounts for 33% of the total mass, the drying shrinkage of 56d carbonized coal gangue concrete is reduced to 1.25×10 -3 .

[0043] Therefore, the present invention has the following advantages over the prior art:

[0044] 1. Realize the recycling of solid waste and solve the soil and water pollution problems caused by coal gangue;

[0045] 2. Coal gangue can absorb free water, which can reduce drying shrinkage and improve compressive strength;

[0046] 3. Through carbonization operation, cement and coal gangue are carbonized at the same time to improve density and reduce chloride ion flux. BRIEF DESCRIPTION OF THE DRAWINGS DETAILED DESCRIPTION

[0047] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0048] Example 1

[0049] A carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue, the raw materials and their mass percentages are: alkali slag: 10-20%, coal gangue: 20-40%, cement: 40-60%, calcium sulfate: 5-15%, deionized water: 5-15%, and the total mass is 100%;

[0050] The composition and mass percentage of the alkali residue are: 60-65% calcium carbonate, 10-15% calcium chloride, 28-15% calcium hydroxide, and the calcium content is 60-80%; the particle size of the alkali residue is not more than 75 μm;

[0051] The role of the alkali residue in the technical solution is that it is rich in calcium and forms active calcium hydroxide during the preparation process;

[0052] The alkali residue is pre-treated, that is, dechlorinated to obtain chlorine-free alkali residue, and the chlorine content of the chlorine-free alkali residue is less than 0.3%.

[0053] The composition and mass percentage of the coal gangue are: 30-60% silicon dioxide, 15-35% aluminum oxide, 2-10% iron oxide, 1-10% calcium oxide, and 10-30% carbonaceous matter; the particle size of the coal gangue is not greater than 5 mm;

[0054] The role of the coal gangue in the technical solution is that silicon dioxide and aluminum oxide, as active substances, have volcanic ash activity and hydraulic gelling properties. During the cement hydration process, they can react with calcium hydroxide in cement to generate a gelling substance, thereby improving the strength and durability of cement.

[0055] The coal gangue is pre-treated, that is, ground by a ball mill to obtain coal gangue powder, and the powder density of the coal gangue powder is 2.0-2.5g / cm 3 , specific surface area 300-600m 2 / Kg.

[0056] The cement is 42.5 grade ordinary Portland cement;

[0057] A method for preparing carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue comprises the following steps:

[0058] Step 1, pretreatment of raw materials, pretreatment of raw materials alkali residue, coal gangue, cement, and calcium sulfate;

[0059] Step 1.1, pretreatment of alkali residue and calcium sulfate, first, washing the alkali residue with water at a water-solid ratio of 6:1 and washing times for 3 times to obtain chlorine-free alkali residue, then calcining the chlorine-free alkali residue at a calcination temperature of 850°C and a calcination time of 45 minutes, wherein the by-product hydrogen chloride produced by the calcination can be recycled, and finally, washing the calcined product with water to obtain calcium hydroxide, and then mixing calcium hydroxide and calcium sulfate at a mass ratio of calcium hydroxide to calcium sulfate of 3:2 to obtain an activator;

[0060] Step 1.2, pretreatment of coal gangue, first, placing the coal gangue and deionized water in a hot stuffing tank, and under closed conditions, hot stuffing temperature of 1000 ° C, hot stuffing aging the coal gangue, so that the active silica and alumina in the coal gangue fully react to generate a gelling substance, thereby improving the stability of the coal gangue, and then, under air conditions, at a ball milling speed of 18r / min and a ball milling time of 5h, the coal gangue is ball milled to obtain coal gangue powder;

[0061] Step 2, preparation of coal gangue concrete slurry, with the coal gangue powder obtained in step 1.2 accounting for 33% of the total mass, cement and coal gangue powder are mixed, and stirred under the condition of stirring time of 15 minutes to obtain a multi-component admixture mixture, referred to as the mixture, and then, the mixture and deionized water are mixed at a mass ratio of 1:0.5, and stirred under the condition of stirring time of 25 minutes to obtain coal gangue concrete slurry;

[0062] Step 3, labeling and curing of the gangue concrete slurry, first, the gangue concrete slurry obtained in step 2 is molded, and then cured under standard curing conditions. After the curing is completed, it is naturally dried indoors for 2 days to obtain gangue concrete, referred to as D165-M56, wherein the basic rule of naming in the present invention is that D is the first letter of Dosage, M is the first letter of Maintenance, and C is the first letter of Carbonization;

[0063] The standard curing conditions are: the curing temperature is 20±2°C, the relative humidity is above 95%, and the curing time is 56 days;

[0064] In order to prove the corrosion rate of steel bars in gangue concrete, a chloride ion flux test was carried out; at the same time, for comparison, a chloride ion flux test was carried out on concrete prepared without adding gangue.

[0065] The method for preparing concrete without adding coal gangue, the steps not specifically described are the same as the method for preparing coal gangue concrete in Example 1, except that: step 1.2 is not required, and in step 2, no coal gangue is added, and the material obtained in step 3 is referred to as D0-M56.

[0066] In order to ensure the requirements of the controlled variables, the mass ratio of coal gangue was changed while keeping the water-binder ratio at 0.4 and the mass ratio of alkali slag and deionized water at 3:2.

[0067] The specific method of chloride ion flux test is to use the coulometric method. First, the sample to be tested is made into a standard specimen with a thickness of 50±3mm and a diameter of 95±5mm. Then, the standard specimen is subjected to the first stage of curing at a curing temperature of 20±5°C, a curing humidity of more than 95%, and a curing time of 1 day. After that, it is placed in a saturated calcium hydroxide solution for curing at a curing temperature of 20±3°C and a curing time of 27 days. The standard specimen is subjected to the second stage of curing. The total curing time is 28 days. After the curing is completed, the standard specimen is vacuum saturated with water. Finally, the saturated specimen is installed in the flux test device so that the two ends of the specimen are connected to the positive and negative electrode solution containers respectively. The standard specimen is subjected to a flux test under the conditions that the negative electrode is a 3.0% sodium chloride solution, the positive electrode is a 0.3 mol / L sodium hydroxide solution, and the test time is 6h.

[0068] The test results of chloride ion flux are shown in Table 1.

[0069] The electric flux of D0-M56 is 1300 Coulombs;

[0070] The electric flux of D165-M56 is 3050 Coulombs;

[0071] The test results of D0-M56 and D165-M56 show that the addition of coal gangue leads to an increase in the chloride ion flux, which is the role of coal gangue in the technical solution. The reason is that coal gangue contains active alumina and active silica, which will change the chemical composition and pH value of the pore fluid in the process of reacting with the cement hydration product calcium hydroxide to form hydration products, affecting the existence form and activity of chloride ions, thereby causing the chloride ions originally adsorbed on the surface of cement particles or in the hydration products to be released back into the pore fluid, increasing the number of freely mobile chloride ions, and ultimately leading to an increase in chloride ion flux. The test results show that the addition of coal gangue has a negative effect on the performance of concrete.

[0072] Table 1 Uncarbonated cement chloride ion flux table

[0073]

[0074] In order to prove the strength of coal gangue concrete, the test block method was carried out. At the same time, for comparison, the concrete prepared without adding coal gangue was tested by the test block method.

[0075] In order to ensure the requirements of controlled variables, the mass ratio of coal gangue was changed while keeping the water-binder ratio at 0.4 and the mass ratio of alkali slag and deionized water at 3:2.

[0076] The specific method of the test block method is as follows: first, the sample to be tested is made into a standard specimen with a size of 150×150×150mm, and then, the standard specimen is subjected to a compression test at a loading speed of 0.8MPa / s until the standard specimen is destroyed. Finally, the compressive strength is calculated based on the specimen failure load and the bearing area. The specific calculation formula is fcc=F / A, where fcc is the compressive strength of the concrete cube specimen, in MPa, F is the specimen failure load, in N, and A is the specimen bearing area.

[0077] The test results of the test block method are shown in Table 2.

[0078] The compressive strength of D0-M56 is 71.1MPa;

[0079] The compressive strength of D165-M56 is 58.5MPa;

[0080] The test results of D0-M56 and D165-M56 show that the addition of coal gangue leads to a decrease in compressive strength, which is the role of coal gangue in the technical solution. The reason is that coal gangue contains soluble salts, such as sulfate, which react with tricalcium aluminate in cement to form calcium sulfonate, which directly causes the cement paste to expand and cause cracks inside the structure. In addition, it consumes part of the tricalcium aluminate, affecting the normal hydration reaction, thereby reducing the compressive strength.

[0081] Table 2 Uncarbonized compressive strength

[0082]

[0083] In order to prove the shrinkage rate of coal gangue concrete, a drying shrinkage test was carried out; at the same time, for comparison, a drying shrinkage test was carried out on concrete prepared without adding coal gangue.

[0084] In order to ensure the requirements of the controlled variables, the mass ratio of coal gangue was changed to carry out drying shrinkage test while keeping the water-binder ratio at 0.4 and the mass ratio of alkali slag and deionized water at 3:2.

[0085] The specific method of the drying shrinkage test is as follows: first, the sample to be tested is made into a standard specimen with a size of 25×25×280 mm, and then the standard specimen is exposed to a temperature of 20±3°C and a RH of 60% for exposure times of 1 day, 3 days, 7 days, 28 days and 56 days, and the length change of the standard specimen is measured.

[0086] The drying shrinkage test results are shown in Table 3.

[0087] The drying shrinkage of D0-M56 is 2.25×10 -3 ;

[0088] The drying shrinkage of D165-M56 is 1.95×10 -3 ;

[0089] The test results of D0-M56 and D165-M56 show that adding coal gangue can reduce the drying shrinkage rate, that is, the role of coal gangue in the technical solution. The reason is that coal gangue can absorb free water in cement paste, that is, reduce the content of free water in cement paste, and achieve the role of internal curing during the drying process, thereby reducing water evaporation and ultimately achieving the effect of reducing drying shrinkage rate.

[0090] Table 3 Drying shrinkage

[0091]

[0092] Step 4, carbon dioxide carbonization of coal gangue concrete, first, placing 25 mm thick wet sand at the bottom of the carbonation box, then carbonizing with carbon dioxide under carbon dioxide gas conditions, referred to as carbonization, to obtain carbonized coal gangue concrete, referred to as D165-M56-C4;

[0093] The carbonization conditions are as follows: a carbon dioxide concentration of 20%±3%, a relative humidity of more than 95%, a carbonization temperature of 20±5° C., and a carbonization time of 4 hours.

[0094] In order to prove the corrosion rate of steel bars in carbonized gangue concrete, a chloride ion flux test was carried out. At the same time, for comparison, a chloride ion flux test was carried out on the carbonized concrete prepared without adding gangue.

[0095] The method for preparing carbonized concrete without adding coal gangue, the steps not specifically described are the same as the method for preparing carbonized coal gangue concrete in Example 1, except that: step 1.2 is not required, and in step 2, no coal gangue is added, and the material obtained in step 4 is referred to as D0-M56-C4.

[0096] The test results of chloride ion flux are shown in Table 4.

[0097] The electric flux of D0-M56-C4 is 750 Coulombs;

[0098] The electric flux of D165-M56-C4 is 1200 Coulombs;

[0099] The test results of D0-M56-C4 and D165-M56-C4 show that under carbonization conditions, the addition of coal gangue will also lead to an increase in chloride ion flux, that is, the role of coal gangue in the technical solution is basically consistent with the conclusions obtained from the chloride ion flux test in step 3;

[0100] Further comparison of D0-M56 and D0-M56-C4 obtained in step 3, that is, the carbonization effect without adding coal gangue, shows that the carbonization operation can reduce the electric flux, and the specific degree of reduction is that the electric flux after carbonization is 57.6% of that before carbonization. The reason is that calcium hydroxide exists in the composition of cement. Therefore, during the carbonization process, calcium hydroxide reacts with carbon dioxide to form calcium carbonate, which fills the pores inside the cement, refines the pores, and improves the density, thereby reducing the migration channel of chloride ions, hindering their diffusion, and finally reducing the chloride ion electric flux; through the above analysis, it can be seen that the carbonization operation can reduce the electric flux, that is, the role of the carbonization operation in the technical solution;

[0101] Similarly, the D165-M56 obtained in step 3 and D165-M56-C4 are compared, that is, the carbonization effect of adding coal gangue shows that the carbonization operation can also reduce the electric flux, and the specific reduction degree is that the electric flux after carbonization is 39.3% of that before carbonization; the test results also support the role of carbonization operation in the technical solution, but through quantitative analysis, it can be seen that adding coal gangue can improve the carbonization effect, and the reduction degree is reduced from 57.6% to 39.3%. The reason is that due to the presence of SiO2 and Al2O3 in the active ingredients in coal gangue, when the carbonization operation is performed after adding coal gangue, the coal gangue and the cement hydration product Ca(OH)2 undergo a secondary hydration reaction to generate more gel products, which can further fill the internal pores of the cement and improve the density, so as to obtain a better effect of reducing the electric flux.

[0102] Table 4 Cement chloride ion flux table

[0103]

[0104]

[0105] In order to prove the strength of carbonized coal gangue concrete, the test block method was carried out. At the same time, for comparison, the test block method was carried out on the carbonized concrete prepared without adding coal gangue.

[0106] The test results of the test block method are shown in Table 5.

[0107] The compressive strength of D0-M56-C4 is 72.9MPa.

[0108] The compressive strength of D165-M56-C4 is 75.9MPa.

[0109] The test results of D0-M56-C4 and D165-M56-C4 show that under carbonization conditions, adding coal gangue can improve the compressive strength. The reason is that there are SiO2 and Al2O3 in the coal gangue. After adding coal gangue, hydrated calcium silicate gel products are generated under carbonization conditions and fill the pores of the material, serving as a skeleton structure to enhance the compressive strength.

[0110] Further comparison of D0-M56 and D0-M56-C4 obtained in step 3 shows that the carbonization effect without adding coal gangue shows that the carbonization operation can improve the compressive strength. Specifically, the compressive strength after carbonization is slightly increased by 2.5% compared with that before carbonization. The reason is basically the same as reducing the electric flux. Specifically, the calcium carbonate generated by the calcium hydroxide in the cement composition during the carbonization process can not only fill the pores inside the cement, but also form a relatively hard carbonized layer on the cement surface, thereby improving the hardness and wear resistance of the cement surface, and then improving the compressive strength; Through the above analysis, it can be seen that the carbonization operation can slightly improve the compressive strength, that is, the role of the carbonization operation in the technical solution;

[0111] However, by comparing D165-M56 and D165-M56-C4 obtained in step 3, that is, the carbonization effect of adding coal gangue, it can be seen that under the condition of adding coal gangue, the carbonization operation has a significantly improved effect on improving the compressive strength. The specific degree of improvement is that the compressive strength after carbonization is significantly increased by 22.9% compared with that before carbonization; the test results not only support the role of carbonization operation in the technical solution, but also, through quantitative analysis, it can be seen that adding coal gangue can improve the carbonization effect, and the degree of improvement in compressive strength increases from 2.5% to 22.9%. The reason is as mentioned above. Compared with the calcium hydroxide in the composition of cement, the gel product generated by the presence of SiO2 and Al2O3 in the coal gangue composition during the carbonization operation has a better filling effect on the pores, that is, it can form a denser structure, thereby significantly improving the compressive strength.

[0112] Table 5 Carbonization compressive strength table

[0113]

[0114]

[0115] In order to demonstrate the effect of carbonization time on performance, comparative examples 1 and 2 are provided, which are carbonized coal gangue concrete prepared with carbonization times of 2h and 4h, respectively, under the same curing time conditions; at the same time, reference example 1 is provided, which is a coal gangue concrete prepared with a carbonization time of 0h without carbonization in step 4 under the same curing time conditions as a basic reference.

[0116] Reference Example 1

[0117] A coal gangue concrete prepared with a carbonization time of 0h, the steps not specifically described are the same as those in Example 1, except that: in the step 3, the curing time is 1 day, and step 4 is not performed. The obtained material is referred to as D165-M1-C0.

[0118] The test results of the test block method of D165-M1-C0 are shown in Table 6. The compressive strength of D165-M1-C0 is 18.4 MPa.

[0119] Comparative Example 1

[0120] A carbonized coal gangue concrete prepared with a carbonization time of 2 hours, the steps not specifically described are the same as those in Example 1, except that: in the step 3, the curing time is 1 day, and in the step 4, the carbonization time is 2 hours. The obtained material is referred to as D165-M1-C2.

[0121] The test results of the test block method of D165-M1-C2 are shown in Table 6. The compressive strength of D165-M1-C2 is 26.9 MPa.

[0122] Comparative Example 2

[0123] A carbonized coal gangue concrete prepared with a carbonization time of 4 hours, the steps not specifically described are the same as those in Example 1, except that: in the step 3, the curing time is 1 day, the step 4 is unchanged, that is, the carbonization time is 4 hours, and the obtained material is referred to as D165-M1-C4.

[0124] The test results of the test block method of D165-M1-C4 are shown in Table 6. The compressive strength of D165-M1-C4 is 31.2 MPa.

[0125] Table 6 1d curing compressive strength table

[0126]

[0127] It can be seen from Reference Example 1, Comparative Example 1 and Comparative Example 2 that increasing the carbonization time can increase the compressive strength. The reason is basically the same as the aforementioned carbonization effect. Increasing the carbonization time can allow the active ingredient calcium hydroxide in cement and the active ingredients SiO2 and Al2O3 in coal gangue to fully react with CO2 to form calcium carbonate and gel products, thereby improving the compressive strength; however, if the carbonization time is too long, excessive calcium carbonate will destroy the mineral composition and structure of the cement from the internal pores of the cement, causing the structure of the hydration product to be destroyed, resulting in a decrease in the compressive strength.

[0128] In order to demonstrate the influence of the amount of gangue added on the performance, comparative examples 3, 4, 5 and 6 are provided. Under the same curing time and carbonization time conditions, the carbonized gangue concrete is prepared with the gangue added accounting for 30%, 36% and 39% of the total mass respectively; at the same time, reference example 2 is provided as a basic reference, in which no gangue is added, that is, the carbonized gangue concrete is prepared with the gangue added amount being 0% under the same curing time and carbonization time conditions.

[0129] Reference Example 2

[0130] A carbonized coal gangue concrete prepared with 0% coal gangue addition, the steps not specifically described are the same as those in Example 1, except that: in step 2, the coal gangue addition amount is 0%, and the obtained material is referred to as D0-M56-C4.

[0131] The electric flux test results of D0-M56-C4 are shown in Table 4. The electric flux of D0-M56-C4 is 750 Coulombs.

[0132] The test results of the test block method of D0-M56-C4 are shown in Table 5. The compressive strength of D0-M56-C4 is 72.9 MPa.

[0133] Comparative Example 3

[0134] A carbonized coal gangue concrete prepared with 30% coal gangue addition, the steps not specifically described are the same as those in Example 1, except that: in step 2, the coal gangue addition amount is 30%, and the obtained material is referred to as D150-M56-C4.

[0135] The electric flux test results of D150-M56-C4 are shown in Table 4. The electric flux of D150-M56-C4 is 1050 Coulombs.

[0136] The test results of the test block method of D150-M56-C4 are shown in Table 5. The compressive strength of D150-M56-C4 is 75.3 MPa.

[0137] Comparative Example 4

[0138] A carbonized coal gangue concrete prepared with 33% coal gangue addition, the steps not specifically described are the same as those in Example 1, except that: in step 2, the coal gangue addition amount is 33%, and the obtained material is referred to as D165-M56-C4.

[0139] The electric flux test results of D165-M56-C4 are shown in Table 4. The electric flux of D165-M56-C4 is 1200 Coulombs.

[0140] The test results of the test block method of D165-M56-C4 are shown in Table 5. The compressive strength of D165-M56-C4 is 75.9 MPa.

[0141] Comparative Example 5

[0142] A carbonized coal gangue concrete prepared with 36% coal gangue addition, the steps not specifically described are the same as those in Example 1, except that: in step 2, the coal gangue addition amount is 36%, and the obtained material is referred to as D180-M56-C4.

[0143] The electric flux test results of D180-M56-C4 are shown in Table 4. The electric flux of D180-M56-C4 is 1400 Coulombs.

[0144] The test results of the test block method of D180-M56-C4 are shown in Table 5. The compressive strength of D180-M56-C4 is 65.4 MPa.

[0145] Comparative Example 6

[0146] A carbonized coal gangue concrete prepared with a coal gangue addition amount of 39%, the steps not specifically described are the same as those in Example 1, except that: in the step 2, the coal gangue addition amount is 39%, and the obtained material is referred to as D195-M56-C4.

[0147] The electric flux test results of D195-M56-C4 are shown in Table 4. The electric flux of D195-M56-C4 is 2350 Coulombs.

[0148] The test results of the test block method of D195-M56-C4 are shown in Table 5. The compressive strength of D195-M56-C4 is 42.6 MPa.

[0149] The following two conclusions can be drawn from Reference Example 2, Example 1, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 6:

[0150] 1. Regarding the electric flux, increasing the amount of coal gangue added will lead to an increase in the chloride ion electric flux, so the amount of coal gangue added should be reduced;

[0151] 2. Regarding compressive strength, when the amount of coal gangue added is small, increasing the amount of coal gangue added can improve the compressive strength; when the amount of coal gangue added is excessive, increasing the amount of coal gangue added will reduce the compressive strength;

[0152] Therefore, considering the performance of carbonized coal gangue concrete comprehensively, the performance of carbonized coal gangue concrete is best when the addition amount of coal gangue accounts for 33% of the total mass.

[0153] For the sake of experimental integrity, the complete experimental data are organized in a table as follows:

[0154] Table 7 is a summary table of chloride ion flux;

[0155] Table 8 is a summary table of compressive strength properties;

[0156] Table 9 is a summary table of drying shrinkage.

[0157] Table 7 Summary of chloride ion flux

[0158] serial number Electric flux (Coulombs) serial number Electric flux (Coulombs) D0-M56 1300 D0-M56-C4 750 D150-M56 2450 D150-M56-C4 1050 D165-M56 3050 D165-M56-C4 1200 D180-M56 3600 D180-M56-C4 1400 D195-M56 4950 D195-M56-C4 2350

[0159] Table 8 Summary of mix ratio and compressive strength

[0160] Table 9 Summary of drying shrinkage

[0161]

[0162]

Claims

1. A carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue, characterized in that: The raw materials and mass percentages of carbonized coal gangue concrete are: alkali slag: 10-20%, coal gangue: 20-40%, cement: 40-60%, calcium sulfate: 5-15%, deionized water: 5-15%, and the total mass is 100%; The cement is 42.5 grade ordinary Portland cement; The coal gangue has the function of increasing strength and reducing shrinkage.

2. The carbonized coal gangue concrete according to claim 1, characterized in that: The coal gangue has the following components in percentage by mass: 30-60% silicon dioxide, 15-35% aluminum oxide, 2-10% iron oxide, 1-10% calcium oxide, and 10-30% carbonaceous matter; the particle size of the coal gangue is no greater than 5 mm; The role of the coal gangue in the technical solution is that silicon dioxide and aluminum oxide, as active substances, have volcanic ash activity and hydraulic gelling properties. During the cement hydration process, they can react with calcium hydroxide in cement to generate a gelling substance, thereby improving the strength and durability of cement. The coal gangue is pre-treated, that is, ground by a ball mill to obtain coal gangue powder, and the powder density of the coal gangue powder is 2.0-2.5g / cm 3 , specific surface area 300-600m 2 / Kg.

3. The foamed concrete according to claim 1, characterized in that: The composition and mass percentage of the alkali residue are: 60-65% calcium carbonate, 10-15% calcium chloride, and 28-15% calcium hydroxide; the particle size of the alkali residue is not greater than 75 μm; The alkali residue has a calcium content of 60-80%; The role of the alkali residue in the technical solution is that it is rich in calcium and forms active calcium hydroxide during the preparation process; The alkali residue is pretreated to obtain chlorine-free alkali residue, and the alkali residue is dechlorinated to obtain chlorine-free alkali residue, and the chlorine content of the chlorine-free alkali residue is less than 0.3%.

4. A method for preparing carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue, characterized in that The following steps are involved: Step 1, pretreatment of raw materials, pretreatment of raw materials alkali residue, coal gangue, cement, and calcium sulfate; Step 2, preparation of coal gangue concrete slurry, with the coal gangue powder obtained in step 1.2 accounting for a certain proportion of the total mass, cement and coal gangue powder are mixed, and stirred under certain conditions to obtain a multi-component admixture mixture, referred to as the mixture, and then, the mixture and deionized water are mixed in a certain mass ratio, and stirred under certain conditions to obtain coal gangue concrete slurry; Step 3, standard curing of the gangue concrete slurry, first, the gangue concrete slurry obtained in step 2 is formed, and then cured under standard curing conditions. After the curing is completed, it is naturally dried indoors for 2 days to obtain gangue concrete, referred to as D165-M56; Step 4, carbon dioxide carbonization of gangue concrete, first, place 25 mm thick wet sand at the bottom of the carbonation box, then perform carbonization under carbon dioxide gas conditions, referred to as carbonization, to obtain carbonized gangue concrete, referred to as D165-M56-C4.

5. The preparation method according to claim 4, characterized in that: The step 1 includes pretreatment of alkali residue and calcium sulfate and pretreatment of coal gangue, specifically, Step 1.1, pretreatment of alkali residue and calcium sulfate, first, washing the alkali residue with water under certain conditions to obtain chlorine-free alkali residue, then calcining the chlorine-free alkali residue under certain conditions, wherein the by-product hydrogen chloride produced by the calcination can be recycled, and finally, washing the calcined product with water to obtain calcium hydroxide, and then mixing the calcium hydroxide and calcium sulfate in a certain mass ratio to obtain an activator; Step 1.2, pretreatment of coal gangue, first, place the coal gangue and deionized water in a hot stuffy tank, and under certain conditions, heat-suffocate the coal gangue to fully react the active silica and alumina in the coal gangue to generate a gelling substance, thereby improving the stability of the coal gangue. Then, under certain conditions, ball-mill the coal gangue to obtain coal gangue powder.

6. The preparation method according to claim 5, characterized in that: In the step 1.1, the water washing condition is a water-to-solid ratio of 6:1, and the number of water washings is 3-5 times; In the step 1.1, the calcination conditions are: the calcination temperature is 850-1000°C, and the calcination time is 45-60min; In the step 1.1, the mass ratio of calcium hydroxide to calcium sulfate is 3:

2.

7. The preparation method according to claim 5, characterized in that: In the step 1.2, the heat-stuffing aging condition is, under a closed condition, a heat-stuffing temperature of 100-300° C.; In the step 1.2, the ball milling conditions are: under air conditions, the ball milling speed is 150-300 r / min, and the ball milling time is 4-5 h.

8. The preparation method according to claim 4, characterized in that: In step 2, the coal gangue powder accounts for 33-39% of the total mass; In step 2, the stirring condition for preparing the mixture is that the stirring time is 15-20 minutes; The mixing conditions for preparing the coal gangue concrete slurry are as follows: the mixing time is 25-30 minutes; In the step 2, the mass ratio of the mixture to deionized water is 1:0.

5.

9. The preparation method according to claim 4, characterized in that: In step 3, the standard curing conditions are: the curing temperature is 20±2°C, the relative humidity is above 95%, and the curing time is 56 days; In step 4, the carbonization conditions are: a carbon dioxide concentration of 20%±3%, a relative humidity of more than 95%, a carbonization temperature of 20±5° C., and a carbonization time of 4 hours.

10. The carbon dioxide carbonized coal gangue concrete based on alkali slag-coal gangue according to claim 1, characterized in that: When used as carbonized coal gangue concrete, when the addition amount of coal gangue accounts for 33% of the total mass, the chloride ion flux is 1150-1250 Coulombs, the compressive strength is 75.5-76.5MPa, and the drying shrinkage is 1.20-1.30×10 -3 .